Membrane Area Sensitivity Analysis to Achieve Higher CO2 Outlet Concentration - Reformadilaga, Mochammad Rizky; Handogo, Renanto; Anugraha, Rendra Panca (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2025)
Separation using membrane technology offers several benefits such as low energy requirement, simple flow process, and no phase change. Moreover, its process only requires sufficient area suitable for remote and offshore facilities. This research will focus on how to improve CO2 concentration in the membrane-2 output or permeate-2. It will discuss techno-economic and modify 2-stage membrane technology to achieve higher carbon dioxide concentration by evaluating several membranes using ASPEN HYSYS. From the simulation results, it was found that reduced membrane area had the effect of increasing the carbon dioxide concentration in permeate-2 but decreasing the gas flow rate. Lowering the membrane area can increase the concentration of CO2 at permeate-2 from 82.47 to 84.7 - 96 % mol of CO2. Based on the evaluation of several membrane areas, a membrane area of 2.5 m2 was chosen because it can produce 91.78% mol CO2 in permeate-2. From the economic analysis, total annual cost could reduce up to USD 1,426,296.